What do we understand from clinical and mechanistic studies on acupuncture treatment for hypertension? - Cheng, Ling (Chin Med, 2015)
The outcome of acupuncture on hypertension treatment is inconclusive. This study aims to evaluate the influence of acupuncture on hypertension, based on findings from mechanistic studies over the course of decades particularly those conducted at the University of California, Irvine. Low-current and low-frequency electroacupuncture (EA) at P5–6 (overlying the median nerve) and S36–37 (overlying the deep peroneal nerve) reduced high blood pressure in a subset of patients (~70 %) with mild-to-moderate hypertension, in a slow-onset (4–8 weeks) but long-lasting (1–2 months) manner. EA inhibited cardiovascular sympathoexcitatory neurons through activation of neurons in the arcuate nucleus of the hypothalamus, the ventrolateral periaqueductal gray in the midbrain and the nucleus raphe pallidus in the medulla, through inhibiting the activity of premotor sympathetic neurons in the rostral ventrolateral medulla (rVLM). Several neurotransmitters such as glutamate, acetylcholine, opioids, GABA, nociceptin, serotonin and endocannabinoids were involved in this EA-induced hypotensive response. The long-lasting inhibition of hypertension induced by EA was related to opioids and GABA in the rVLM, neural circuitry between the arcuate and ventrolateral periaqueductal gray, and prolongation of the increase in preproenkephalin mRNA levels and enkephalin levels in the rVLM and arcuate. Moreover, the long-lasting inhibition of sympathetic activity by EA was confirmed in EA-treated hypertensive patients with decreased levels of norepinephrine, renin and aldosterone.